Three Yersinia enterocolitica AmpD Homologs Participate in the Multi-Step Regulation of Chromosomal Cephalosporinase, AmpC - Liu, Chang; Wang, Xin; Chen, Yuhuang; Hao, Huijing; Li, Xu; Liang, Junrong; Duan, Ran; Li, Chuchu; Zhang, Jing; Shao, Shihe; Jing, Huaiqi (Frontiers in Microbiology, 2016)
In many gram negative bacilli, AmpD plays a key role in both cell well recycling pathway and β-lactamase regulation, inactivation of the ampD causes the accumulation of 1,6-anhydromuropeptides and results in the ampC overproduction. In Yersinia enterocolitica, the regulation of ampC expression may also relys on the ampR-ampC system, the role of AmpD in this species is still unkonwn. In this study, three AmpD homologues (AmpD1, AmpD2 and AmpD3) have been identified in complete sequence of strain Yersinia enterocolitica subsp. palearctica 105.5R(r). To understand the role of three AmpD homologues, several mutant strains were constructed and analyzed where a rare ampC regulation mechanism was observed: low-effective ampD2 and ampD3 cooperate with the high-effective ampD1 in the three levels regulation of ampC expression. Enterobacteriaceae was used to be supposed to regulate ampC expression by two steps, three steps regulation was only observed in Pseudomonas aeruginosa. In this study, we first reported that Enterobacteriaceae Y.enterocolitica can also possess a three steps stepwise regulation mechanism, regulating the ampC expression precisely.